Pathological complete response in advanced gastrointestinal stromal tumor after imatinib therapy - Melichar, Bohuslav; Vobořil, Zbyněk; Nožička, Jan; Ryška, Aleš; Klozová-Urminská, Hana; Vaněček, Tomáš; Michal, Michal (Internal medicine, 2005)
Gastrointestinal stromal tumor (GIST) is a rare neoplasm exhibiting, in most cases, mutations of c-kit. Recently it has been demonstrated that a majority of GIST patients with c-kit mutations respond to therapy with imatinib, a c-kit tyrosine kinase inhibitor. Although the response rate in patients treated with imatinib in prospective clinical studies is above 50%, complete response is rare, and the data on the use of imatinib as neoaduvant therapy facilitating radical surgery is still scanty. Here, we report on a patient with metastatic gastric GIST who underwent surgery after 6 months of imatinib therapy. No tumor cells were detected on pathological examination of resection specimen. This case report indicates that a pathological complete response could be achieved with imatinib therapy in patients with GIST, but a wider experience and longer follow-up is necessary to appreciate the prognostic significance of pathological complete response in GIST.
Keywords: počítačová rentgenová tomografie; nádory jater; gastrektomie; Humans; lidé středního věku; pyrimidiny; Gastrectomy; následné studie; Stomach; Antineoplastic Agents; financování organizované; Financing, Organized; lidé; tyrosinkinasy; Liver Neoplasms; gastrointestinální stromální tumory; Gastrointestinal Stromal Tumors; Male; Protein-Tyrosine Kinases; Middle Aged; Tomography, X-Ray Computed; žaludek; piperaziny; protinádorové látky; Piperazines; Pyrimidines; mužské pohlaví; Follow-Up Studies